Tacrolimus Intrapatient Variability After Switching From Immediate or Prolonged-Release to Extended-Release Formulation, After an Organ Transplantation - Del Bello, Arnaud; Gaible, Clotilde; Longlune, Nathalie; Hebral, Anne-Laure; Esposito, Laure; Gandia, Peggy; Kamar, Nassim (Frontiers in Pharmacology, 2021)
Background and Purpose: Several formulations of tacrolimus (tac) are available, but evidence of the benefit of changing to the most recent formulations is lacking. Tacrolimus Intra-Patient Variability (tac-IPV) is an emerging risk factor associated with poor graft outcomes after solid organ transplantations. Here, we examined the modifications of tac-IPV after switching to a different formulation of tacrolimus. Experimental Approach: We analyzed, in a cohort of 353 solid organ transplant recipients, the clinical consequences and tac-IPV during the year before and after switching from immediate-release (IR-tac) or prolonged-release tacrolimus (PR-tac) to extended-release tacrolimus (ER-tac). Key Results: The tac-IPV – estimated by the Coefficient of Variation (CV- IPV) and the CV-IPV normalized by the dose, CV (C0/D) IPV – was stable before and after the switch to ER-tac (CV-IPV: 19 (0-79) % before, 18 (0-90) % after the switch, p=0.64 and CV(C0/D)-IPV: 22 (1-100) % before, 22 (1-90) % after the switch, p= 0.80). However, we found that patients with a higher tac-IPV with IR or PR-tac (i.e. >75th percentile of CV-IPV, or CV (C0/D) IPV) presented a dramatical decrease of variability after the switch (CV (C0/D) IPV 43 (33-100) % with IR-tac or PR-tac and 17 (1-68) % after the switch to ER-tac, p < 0.0001). Conclusion and Implications: The CV-tac IPV was stable for the majority of patients treated with IR, PR, or ER-tac formulations. However, our study suggests that patients with the highest CV-IPV could benefit from switching to the ER-tac formulation.